Science fair projects : helping your child create a super science fair project - Barry, Dana M.; Chaney, Howard; Smith, Robert W. (Westminster, CA : Teacher Created Materials, 2000)
Provides information on how to successfully prepare children for science fair experiences, with project ideas and work sheets, planning and presentation activities, and sample investigations based on the traditional problem-solving model.
Science Books & Films (A.A.A.S.).
4.7
3-6
Keywords: Science projects -- Juvenile literature; Science -- Experiments -- Juvenile literature; Experiments; Science projects; Science projects; Science -- Experiments